17. Nasal irritation of Mui Xoang Nhat Nhat spray in experimental animals - Anh, Pham Thi Van; Thuy, Nguyen Thi; Hoai, Nguyen Quoc; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2024)
Mui xoang Nhat Nhat (MXNN) spray is a herbal combination of Angelica dahurica, Xanthium strumarium L., Ageratum conyzoides L, which is intended to use as the supportive treatment of stuffy nose, runny nose in some upper respiratory diseases such as rhinitis and sinusitis. This study was carried out to evaluate the nasal mucosa irritation of MXNN spray in experimental animals. Rabbits were divided into 3 groups: group 1 administered 0.9% sodium chloride, group 2A and 2B administered MXNN spray 2 puffs for each nostril, 3 times a day for 5 days. The investigational product was discontinued for 7 days for Group 2B rabbits to evaluate the recovery from the lessions. At the end of the experimental period, the rabbits were grossly and microscopically evaluated. Our results showed that MXNN spray caused slight irritation, which might cause vascular congestion in the submucosa layer and could be mostly recovered in a week in rabbits.